Business education in Australia: COVID-19 and beyond. Issue 6 (2nd November 2021) - Hogan, Owen; Charles, Michael B.; Kortt, Michael A.
ABSTRACT: COVID-19 has significantly impacted Australia's attractiveness as an international study destination and affected public university budgets, which have increasingly relied on attracting international students through business education. The notion of business schools as an onshore export business has long been a constraint to business schools' claims of public legitimacy. COVID-19 has effectively removed the 'cash cow' status, meaning business schools must turn to other sources of support and legitimacy to secure their future. A Delphi of expert panel members was conducted to determine how this and other key drivers of change will impact business education in Australia over the next 10 years. It is clear from the findings that public business education is now irrevocably changed and that, without dramatic shifts in policy and strategy, it will confront even more significant challenges to its legitimacy into the future.